Biorefining microalgae and plant hosts with extraction, recovery, and purification of multiple biomolecules - Dixon, Chelsea Keiana (Kansas State University, 2018)
Microalgae are a potential feedstock for renewable and sustainable bioproducts and energy but there are significant scientific and engineering challenges to address before widespread acceptance of this platform. In particular, biorefining microalgae serves to maximize biomass valorization and minimize waste to improve process economics. The overall goal of this dissertation was the development of a biological-based microalgae biorefinery to enhance the economic feasibility of Chlamydomonas reinhardtii as a source of multiple products including native proteins and lipids. Specific objectives included accumulating biomass enriched in target biomolecules and determining processing strategies that eliminated the need to dry biomass, employed mild conditions to maintain extractability and quality, and minimized application of petroleum-derived and toxic solvents during extraction. The microalgae biorefinery developed included biomolecule accumulation, biomass harvesting, and targeted enzymatic degradation of the cell wall and organelles for release of native proteins and lipids. Biomass was cultivated, and kinetic studies indicated that 48 h nitrogen deprivation was adequate for protein and lipid accumulation. Four lytic enzymes were screened for their ability to permeate the C. reinhardtii cell wall and the C. reinhardtii-produced enzyme, autolysin, led to >85% cell disruption. TEM imaging confirmed cell disruption and retention of lipid droplets in organelle remnants indicating that protein, lipids, and starch could be distinctly partitioned and recovered. A design of experiments optimization study determined that incubation of disrupted biomass at pH 12 for 4 h at 45°C resulted in up to 65% of total protein released from disrupted biomass followed by 40-50% protein recovery with isoelectric precipitation. The cell disruption and protein extraction steps were subsequently integrated to minimize unit operations, processing time, and energy inputs. Secondary application of trypsin led to release of ~73% of total lipids (enriched in triacylglycerols) from the disrupted biomass. Characterization by thin layer chromatography and GC-FID of released lipids revealed similar profiles of enzymatically released lipids as compared to those released by conventional extraction procedures. Finally, the composition of released lipids indicated favorable combustion behavior, high oxidation stability, and suitability as biodiesel. The developed biological-based biorefinery is a promising step towards adoption of microalgae as a source of bioproducts to provide energy and food to meet the needs of a growing population. The second focus of the work was mitigation strategies for isolation of critical impurities (or potential co-products) while processing microalgae and plant hosts. Specific emphasis was placed on evaluating the impact of proteases, polysaccharides, phenolic compounds and pigments, phytic acid, and host cell proteins on the processing of microalgae and other plant hosts for extraction, recovery, and purification of therapeutic proteins. This review served as evaluation of the broader implications of application of the biorefinery to transgenic microalgae and other plants.
Keywords: Microalgae; Processing; Protein extraction; lipid extraction; biorefining